(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to examine the effect of the leadership of banking companies on the implementation of GCG in Indonesia. This study will also investigate the influence of fit and proper test as moderating variable.The method used in this study uses calculation based on Structural Equation Model (SEM). The object of the study was all national commercial banks operating in Indonesia. The respondent in this study was one person from the board of directors at the bank, in which the total respondents were 115 respondents. The results showed that leadership is an important factor in the success of GCG practice. Fit and proper is proven to strengthen the success of GCG practice. Properly implemented governance can ensure the continuity of banking operations.This research will be useful in knowing the results obtained when selecting the right leader through a fit and proper process in the banking sector by considering the indicators examined in this study.